2022
DOI: 10.1108/jcm-04-2021-4593
|View full text |Cite
|
Sign up to set email alerts
|

An integrated framework examining sustainable green behavior among young consumers

Abstract: Purpose Promoting sustainable behavior is an elusive task as it is not an innate and natural response of individuals. While a conducive environment that promotes sustainability arguably plays a prominent role in influencing individuals’ belief structure and norms, not much has been done to examine the interplay between environmental, personal and behavioral domains in sustainable consumption. Drawing on the theoretical perspectives of the social cognitive theory (SCT) and value–beliefs–norms (VBN), this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…Lastly, study results indicated that when compared to sustainable apparel consumption attitudes and perceived descriptive norms, perceived behavioral efficacy was a weaker predictor of sustainable apparel purchase intention, similar to perceived subjective norms. Nonetheless, the ability of behavioral efficacy to explain purchase intention does support relevant research which suggested that the former was a mediator between exposure to social media content promoting green products and product adoption intention (e.g., De Lenne and Vandenbosch, 2017; Jahari et al, 2022). These results serve as a good reminder in that it would be important to explore the factors that may weaken or strengthen behavioral efficacy in adopting sustainable products.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Lastly, study results indicated that when compared to sustainable apparel consumption attitudes and perceived descriptive norms, perceived behavioral efficacy was a weaker predictor of sustainable apparel purchase intention, similar to perceived subjective norms. Nonetheless, the ability of behavioral efficacy to explain purchase intention does support relevant research which suggested that the former was a mediator between exposure to social media content promoting green products and product adoption intention (e.g., De Lenne and Vandenbosch, 2017; Jahari et al, 2022). These results serve as a good reminder in that it would be important to explore the factors that may weaken or strengthen behavioral efficacy in adopting sustainable products.…”
Section: Discussionmentioning
confidence: 88%
“…De Lenne and Vandenbosch (2017) reported that self-efficacy beliefs were a positive mediator between exposure to fashion magazine content and sustainable apparel purchase intention. In an examination of sustainable green behavior among young consumers, Jahari et al (2022) also suggested that perceived self-efficacy mediated the relationship between exposure to green behavior advertisements and proenvironmental behavioral intentions.…”
Section: Behavioral Control and Self-efficacymentioning
confidence: 99%
“…Green hotels are emerging as frontrunners in adopting sustainable practices, causing a profound transformation in the hospitality industry. As consumer preferences shift, there is a greater emphasis on the "go green" movement [ 77 ]. This shift is about more than being environmentally conscious; it is also about improving the overall guest experience.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…These three dimensions can be explained through values orientation, New Environmental Paradigm (NEP), awareness of consequences (AC), ascription of responsibility (AR), and personnel norms (PN). The effect of the variables are transmitted in the forms of chains, forming an interrelated logical causal chain [ [19] , [20] , [21] , [22] ].…”
Section: Literature Reviewmentioning
confidence: 99%